Differences in dietary pattern between obese and eutrophic children - Balthazar, Emilia A. [UNESP]; Oliveira, Maria Rita Marques [UNESP] (Springer Nature, 2011)
Background: Excessive consumption of energy is a decisive factor of obesity, but a simple quantitative assessment of consumption between obese and eutrophic individuals not always explains the problem, raising questions about the importance of the qualitative aspects of food. Therefore, the purpose of this study was to evaluate the differences in nutrient composition and meal patterns between eutrophic and obese schoolchildren. Methods. The diet of 83 children (42 obese and 41 eutrophic), aged between 7 and 11 years of age, was assessed by two non-consecutive dietary recalls. After the software analysis of macro and micronutrients composition, the different types and amount of legumes, fruits and vegetables were analyzed to verify the dietary patterns. Results: No differences were verified in energy consumption between the groups (eutrophic = 1934.2 672.7 kcal, obese = 1835.8 621.2 kcal). In general, children showed consumption within the recommended ranges of carbohydrates, lipids and proteins. The average consumption of fiber was higher in the eutrophic group (20.7 g) when compared to the obese group (14.8 g). The dietary fiber was strongly correlated with the number of servings of beans (r = 0.77), when compared to fruits (r = 0.44) and leafy vegetables (r = 0.13). It was also observed that the higher the consumption of fiber and beans, the lower the proportion of dietary fat (r = -0.22) in the diet. Generally, there was a low consumption of fiber (20.7 g = eutrophic group/14.8 g = obese group), beans (1.1 portions in the eutrophic and obese groups), fruits (0.7 portions eutrophic group and 0.6 obese group) and vegetables (1.3 eutrophic group and 1.1 obese group). Conclusions: It is concluded that the obesity was more related to a dietary pattern of low intake of dietary fiber than excessive energy consumption and macronutrients imbalance. © 2011 de Oliveira et al; licensee BioMed Central Ltd.
Keywords: trace element; caloric intake; child; dietary fiber; Fabaceae; feeding behavior; health; human; metabolism; nutrition; obesity; physiology; Child; Dietary Fiber; Energy Intake; Food Habits; Health; Humans; Micronutrients; Nutritional Physiological Phenomena; Obesity